Behavioral phenotyping of mouse models of neuropsychiatric and neurodevelopmental disorders - Crawley, Jacqueline N. (Henry Stewart Talks, 2015)
Contribution of animal models to biomedical research, Modeling psychiatric diseases, Targeted gene mutations mouse models, Behavioral phenotyping: a three-tiered strategy, General health, neurological reflexes, sensory, motor abilities and specific tests, Mouse models for autism, Key experimental design issues
Reviewed at 2024/07/02